Transcriptome and DNA Methylation Profiles of Mouse Fetus and Placenta Generated by Round Spermatid Injection - Zhu, Haibo; Sun, Hao; Yu, Dawei; Li, Tianda; Hai, Tang; Liu, Chao; Zhang, Ying; Chen, Yurong; Dai, Xiangpeng; Li, Ziyi; Li, Wei; Liu, Ruizhi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Low birth efficiency and developmental abnormalities in embryos derived using round spermatid injection (ROSI) limit the clinical application of this method. Further, the underlying molecular mechanisms remain elusive and warrant further in-depth study. In this study, the embryonic day (E) 11.5 mouse fetuses and corresponding placentas derived upon using ROSI, intracytoplasmic sperm injection (ICSI), and natural in vivo fertilized (control) embryos were collected. Transcriptome and DNA methylation profiles were analyzed and compared using RNA-sequencing (RNA-seq) and whole-genome bisulfite sequencing, respectively. RNA-seq results revealed similar gene expression profiles in the ROSI, ICSI, and control fetuses and placentas. Compared with the other two groups, seven differentially expressed genes (DEGs) were identified in ROSI fetuses, and ten DEGs were identified in the corresponding placentas. However, no differences in CpG methylation were observed in fetuses and placentas from the 3 groups. Imprinting control region methylation and imprinted gene expression were the same between the 3 fetus and placenta groups. Although 49 repetitive DNA sequences (RS) were abnormally activated in ROSI fetuses, RS DNA methylation did not differ between the 3 groups. Interestingly, abnormal hypermethylation in promoter regions and low expression of Fggy and Rec8 were correlated with a crown-rump length less than 6 mm in one ROSI fetus. Our study demonstrates that the transcriptome and DNA methylation in ROSI-derived E11.5 mouse fetuses and placentas were comparable with those in the other two groups. However, some abnormally expressed genes in the ROSI fetus and placenta warrant further investigation to elucidate their effect on the development of ROSI-derived embryos.